Introduction to Chapter 8: How to Address the Borders of a Qualified Medium and to Situate ‘Narrative’ Within Elleström’s Framework - Jensen, Signe Kjaer (Future Directions in Intermediality and Multimodality, 2025)
In this introduction to Leitch’s chapter, Jensen takes her point of departure in Leitch’s focus on narrativity and especially on his choice to examine “less obviously narrative media”. As a background for understanding these “less obviously narrative media”, Jensen discusses Elleström’s definition of ‘narrative’ as a type of ‘virtual sphere’, and his application of narrative to mathematical equations.